ANALISIS DAMPAK DIGITALISASI DALAM MENINGKATKAN EFEKTIFITAS PENGELOLAAN ADMINISTRASI APARATUR KELURAHAN HARAPAN TANI KABUPATEN INDRAGIRI HILIR - Boy Priyadi; Agus Maulana; Dharmasetiawan Dharmasetiawan (KOLABORATIF: Jurnal Isu Sosial dan Tinjauan Kebijakan, 2026)
This study aims to determine the effectiveness of administrative management of Harapan Tani Village Apparatus and to analyze and empirically demonstrate the impact of digitalization on the effectiveness of administrative management, which has implications for public services. The background of this study is based on the importance of apparatus governance in supporting improved service quality to the public. The research method used is quantitative with a descriptive and associative approach. The population in this study was Harapan Tani Village apparatus in Kempas District, with a sample of 42 individuals drawn from the village and staff, as well as neighborhood units (RW) and neighborhood units (RT), each represented by one village apparatus. Data collection was conducted through a questionnaire using a Likert scale (1–5). The data obtained were tested using SPSS, including validity, reliability, classical assumptions, hypothesis testing, t-tests, and coefficients of determination. The regression test results indicate that digitalization has a positive and significant impact on administrative management effectiveness, with a t-value of 6.542 and a significance level of 0.000 <0.05. Furthermore, the coefficient of determination (R²) of 0.587 indicates that the impact of digitalization contributes 58.7% to administrative management effectiveness, while the remaining 41.3% is influenced by factors outside this study. Therefore, it can be concluded that the higher the impact of digitalization on village officials, the greater the effectiveness of administrative management provided to the community